1993
DOI: 10.1149/1.2056247
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Hexavalent Chromium in Aqueous Solutions by Polypyrrole

Abstract: Spontaneous electron transfer, along with anion uptake by doping, form the basis of a new concept for the reduction of toxic Cr(VI) using an electronically conductive polymer, e.g., polypyrrole. Proof of concept experiments are described which show that aqueous sulfuric acid solutions containing 5–100 ppm Cr(VI) can be thus converted at ∼100% efficiency to the environmentally more tractable Cr(III) species at time intervals spanning several minutes. The reversibility of the polymer redox process enables the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 0 publications
2
58
1
1
Order By: Relevance
“…Scans of the solution were obtained every 10 min over a period of 3 h and show the removal of Cr(VI) from the solution. This is consistent with the reduction of Cr(VI) by PPy at other substrates [17][18][19][20][21][22]. The PPy was grown to a thickness of 0.5, 1.0 and 5.0 lm and similar UV-Vis experiments were performed in order to assess the effect of polymer thickness.…”
Section: Methodssupporting
confidence: 79%
See 2 more Smart Citations
“…Scans of the solution were obtained every 10 min over a period of 3 h and show the removal of Cr(VI) from the solution. This is consistent with the reduction of Cr(VI) by PPy at other substrates [17][18][19][20][21][22]. The PPy was grown to a thickness of 0.5, 1.0 and 5.0 lm and similar UV-Vis experiments were performed in order to assess the effect of polymer thickness.…”
Section: Methodssupporting
confidence: 79%
“…Investigated remediation techniques include electrochemical methods [8,9], the use of ferrous iron [7], photocatalysis utilising UV illumination of titanium [10,11] or zinc oxides [12] and a number of other interesting methods including the implementation of copper, hydrogen peroxide, hydrogen sulphide and methylated yeast biomass [13][14][15][16]. In the past number of years the use of conducting polymerbased materials in Cr(VI) remediation has arisen as an interesting area of research [17,18]. Typically, a substrate is coated with a layer of conducting polymer, which is then used to reduce the toxic Cr(VI) to Cr(III), Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that conducting polypyrrole films can be used to reduce Cr(VI), opening up the possibility of a new remediation-control technology [7][8][9][10][11][12]. Polypyrrole (PPy) is a well-known conducting polymer and can undergo good reversibility between its conducting and insulating states.…”
Section: Introductionmentioning
confidence: 99%
“…Cr(III) is also an important micronutrient in the biological activity of insulin, is relatively stable and has low solubility in aqueous solution. The compounds of Cr(III) are reported to be 10-100 times less toxic than those of Cr(VI) (Wei et al 1993).…”
Section: Introductionmentioning
confidence: 99%